Updates in the Treatment of Active and Latent Tuberculosis - Haas, Michelle K.; Belknap, Robert W. (Seminars in Respiratory and Critical Care Medicine, 2018)
First-line therapy for active tuberculosis (TB) has remained unchanged for nearly 40 years. Isoniazid, rifampin, pyrazinamide, and ethambutol for the initial two-month phase followed by isoniazid and rifampin for 4 to 7 months is standard treatment for people at low risk for drug-resistant disease. Directly-observed therapy (DOT) remains the standard of care for pulmonary TB. Virtual treatment monitoring using digital technologies is becoming more common as a way to provide a more patient-centered approach to care. Attempts to shorten treatment duration have been unsuccessful based on recent clinical trials evaluating the role of fluoroquinolones. Treatment-shortening trials using higher doses of rifamycins are currently underway. Recently approved medications for TB treatment are recommended only for drug-resistant disease, but novel agents in varying stages of development are being evaluated. Rifamycin-based regimens for latent TB infection (LTBI) have been successful in preventing progression to TB disease. Once-weekly isoniazid and rifapentine for 12 weeks by DOT was shown to be safe and effective compared with 9 months of isoniazid. The same regimen was shown to have acceptable treatment completion when given self-administered. Newer studies are investigating even shorter LTBI treatment with durations of less than 2 months. Treatment of LTBI in people likely infected with multidrug resistant TB is very limited, but one observational study found that fluoroquinolones appear to be effective. The first randomized trials for treating LTBI in contacts to MDR-TB are currently enrolling.
Keywords: active tuberculosis; latent tuberculosis; treatment; isoniazid; rifampin; rifapentine; directly observed therapy